About the Sikh Shrines: - (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The Sikh Shrine is known as Gurudwara or a home of the Guru where the Guru himself lives. Its most important element is the presence of the Sikh mentors.The Sikh believes that the prayers to God can be done anytime and anywhere. The main purpose of Gurudwara is congregational worship. Even a very small group of devotees inhabiting any place anywhere in world would generally build a temple for them to get together for religious or even for community purposes. The building of gurdwara can be simple which is decided by the local people of society. But the Sikhs would not stint in this matter and they have, therefore built many impressive Gurudwaras, which can accommodate thousands of devotees. Mostly important gurdwara are concerned with the ten Gurus or have other historical associations and are mammoth of pilgrimage.